ANALYSIS OF THE BIOACTIVE AND MICROBIOLOGICAL CONTENTS OF HERBAL MIXTURES SOLD IN ANAMBRA STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Over the years, medicinal plants have played a significant role in traditional medicine practice. The ever-increasing health-related difficulties and the search for possible treatments and likely cures have led to the increasing patronage of herbal drugs in Nigeria. There is an overwhelming increase in the production and distribution of herbal medications, and the trend has instigated concern about the quality of the products being sold in Anambra State, Nigeria. Thus, the primary purpose of the current study is to analyze the microbiological and phytochemical constituents of okanga powder, goko cleanser, and deep root herbal mixtures popularly sold in Nigeria. The phytochemical tests conducted on the herbal products revealed that the herbal products contain alkaloids, flavonoids, glycosides, anthraquinones, tannins, and saponins. The result of the microbial count indicates the presence of varying microorganisms such as S. aureus, E. coli, Salmonella, and Klebsiella spp in the herbal products. The study concludes that herbal products possess active phytochemicals. However, the presence of pathogenic organisms was discovered in the herbal drugs.